2010
DOI: 10.1080/13803390903066873
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral limbic system destruction in man

Abstract: We report here a case study of a rare neurological patient with bilateral brain damage encompassing a substantial portion of the so-called "limbic system." The patient, Roger, has been studied in our laboratory for over 14 years and the current article presents his complete neuroanatomical and neuropsychological profiles. The brain damage occurred in 1980 following an episode of herpes simplex encephalitis. The amount of destroyed neural tissue is extensive and includes bilateral damage to core limbic and para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 58 publications
2
58
1
2
Order By: Relevance
“…That said, the patients in the current study including the patient with an etiology and lesion most similar to L. S. J. (1951) performed notably better than L. S. J. Neuroanatomically, in Patient 1951, the entire hippocampal formation is destroyed in the right hemisphere, and in the left hemisphere, the anterior portion of the hippocampal formation is completely destroyed while 1–2 cm of the posterior hippocampus may have been spared (Feinstein et al, 2010). Furthermore, Patients 1846 and 2363 also have significant reductions in hippocampal volume and severe declarative memory impairment.…”
Section: Discussionmentioning
confidence: 77%
“…That said, the patients in the current study including the patient with an etiology and lesion most similar to L. S. J. (1951) performed notably better than L. S. J. Neuroanatomically, in Patient 1951, the entire hippocampal formation is destroyed in the right hemisphere, and in the left hemisphere, the anterior portion of the hippocampal formation is completely destroyed while 1–2 cm of the posterior hippocampus may have been spared (Feinstein et al, 2010). Furthermore, Patients 1846 and 2363 also have significant reductions in hippocampal volume and severe declarative memory impairment.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have reported difficulties in understanding and considering the feelings of others, as reported by a family member, in a patient who presented with impaired disgust processing and personality changes following a left posterior insular stroke (Borg et al, 2013). In another rare patient with brain damage affecting the insula as well as other limbic and paralimbic structures bilaterally (including the amygdala), impaired recognition of anger expressions co-occurred with marked alterations in social relationships, the patient approaching strangers without regard for social signals (Adolphs et al, 1999;Feinstein et al, 2010). This patient was described as expressing little, if any, negative emotions, although a recent report demonstrated that he could still feel and express pain (Feinstein et al, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…The cingulate gyrus is generally included in the limbic system and the insula plays a vital role as limbic integration cortex [24]. The limbic system is associated with memory and learning, as well as emotions [25]. Moreover, the presence of WMLs is related to affective and emotional dysfunction [22,23,26,27].…”
Section: Discussionmentioning
confidence: 99%